2000
DOI: 10.1016/s1010-7940(99)00356-5
|View full text |Cite
|
Sign up to set email alerts
|

Total endoscopic computer enhanced coronary artery bypass grafting

Abstract: Endoscopic ITA harvesting and performing of arterial anastomoses can be safely performed with the da Vinci system. TECAB is possible on the arrested heart with good functional results. However, a substantial learning curve has to be overcome which is reflected in long operation times and an initial significant conversion rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
134
0
6

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 263 publications
(146 citation statements)
references
References 17 publications
6
134
0
6
Order By: Relevance
“…Falk described the first off-pump robotic TECAB using an endoscopic stabilizing device in 2000. 11) A port access stabilizer was required to achieve TECAB, and thus an EndoWrist stabilizer was mounted on the fourth arm of the da Vinci surgical system. This suction-type endostabilizer gives the console surgeon complete control while offering better exposure and stabilization, and these have led to highly complex endoscopic procedures such as triple and quadruple CABG being performed on arrested and beating hearts.…”
Section: Tecabmentioning
confidence: 99%
“…Falk described the first off-pump robotic TECAB using an endoscopic stabilizing device in 2000. 11) A port access stabilizer was required to achieve TECAB, and thus an EndoWrist stabilizer was mounted on the fourth arm of the da Vinci surgical system. This suction-type endostabilizer gives the console surgeon complete control while offering better exposure and stabilization, and these have led to highly complex endoscopic procedures such as triple and quadruple CABG being performed on arrested and beating hearts.…”
Section: Tecabmentioning
confidence: 99%
“…The utilization of this method, in a revascularization surgery with mini-thoracotomy, reduces the pain in the postoperative period, probably because of less traction of the rib cage. In two different studies, utilizing the da Vinci system reported by MOHR et al [18] and by FALK et al [20], on average 64 ± 64 minutes and 61 ± 27 minutes were required for the dissection of the artery, but this time was reduce to 25 to 40 minutes, respectively, in the last cases of the series. Both demonstrated a mean functioning after anastomosis of greater than 95%.…”
Section: Robotic Surgerymentioning
confidence: 87%
“…Excellent outcomes have been observed in large series (1)(2)(3). Most recently, robotic surgical systems providing true three-dimensional (3-D) vision via dualcamera endoscopes, coupled with multi-jointed microinstrumentation enabling multiple degrees of freedom in range of motion, have been utilized to conduct coronary revascularization (4,5), mitral valve repair (4), atrial septal defect closure (6), left ventricular pacing lead implantation (7) and aortic valve surgery (8). The development of this surgical approach, the advantages, the cardiac surgical applications, the limitations and the potential future applications are discussed here.…”
Section: Introductionmentioning
confidence: 99%